Fatores associados ao intervalo entre o diagnóstico e início do tratamento em pacientes com câncer de boca e de orofaringe no Brasil: uma análise da base de dados nacional - BORGES, Marcio Vinícius Campos (2011)
Oral and Oropharyngeal cancer is one of the cancers which has the highest mortality in the world and the prevention of the treatment delay is a key to decrease this high mortality. The objective of this study was to analyze temporal trends and factors associated to the interval between diagnose of these diseases established from the date of the histopathological report to the beginning of the treatment in Brazil between 2013 and 2019. A retrospective observational study was conducted with secondary data from the Brazilian Health System Database (DATASUS). The analyzed variables were year of treatment, sex, age group, anatomic region, staging of the disease, type of treatment and Federated Unit of Brazil. Thematic maps were created and the statistical analyses was performed using Chi-Square statistics (χ2). The sample of the study was 72,062 cases. The majority of the cases was men (79.32%), people older than 45 (91.15%) and lesions diagnosed in the oropharynx (31.3%) or regions of the tongue (29.3%). The treatment was earlier in young people, lip cancer and surgery treatment. There was high variability through time among the Federated Units of Brazil and just the Brazilian state of Santa Catarina showed decrease in those cases whose treatment had begun after 60 days for both oral and oropharyngeal cancer. Factors such as age group, anatomic region and type of treatment of the oral and oropharyngeal cancer are factors that influenced the interval between the diagnose and beginning of treatment of these diseases in Brazil and there was a decrease in the interval to begin the treatment specially in 2018 and 2019.